Toward a Unified Framework for Maqāṣid al-Qur’ān: The Need for Addressing Fragmentation Through Consensus Building - Tazul Islam (Universiti Sains Islam Malaysia, 2026)
Maʿālim Al-Qurʾān Wa Al-Sunnah, Volume 21 Issue 2 Page (301–330)